Trypanotolerant cattle breeds in Zaire - Mortelmans, J.; Kageruka, P. (1976)
Historical account of the introduction of trypanotolerant cattle breeds to Zaire. Successes achieved under good feeding and management conditions on both large and small farms highlighted. Current developments in N'Dama cattle breeding in the region and their extension to the new land areas reviewed.